O planejamento e a atividade principal da criança: vivências de futuras professoras na educação infantil - Marafiga, Andressa Wiedenhoft (2017)
Early Child Education, mathematics education, main activity of the child and planning. Based on these concepts that arises the justification of this research which is bound up to Marters in Education of Universidade Federal de Santa Maria (UFSM). Firstly, from the enchantment of Early Child Education by the researcher; secondly, from the concernin in considering the main activity of the child, the game, in the teaching planning and, thirdly, as future teachers understand this relation. In light of this, we stablished the main purpose of this study that is to investigate the formative process of future teachers in the organization of teaching in Early Child Education. The present study was conducted within the scope of PIBID (Programa Institucional de Bolsas de Iniciação à Docência), specifically of the Subprojeto Interdisciplinar Educação Matemática (PIBID/InterdEM) of Universidade Federal de Santa Maria (UFSM), that was created in 2014. For this study, we count of the collaboration of four undergraduation students of Pedagogy (UFSM) and Special Education (UFSM), who planned, organized and developed teaching actions in a municipal school in Santa Maria (RS), which was a partner of the subproject of PIBID. This research was conducted based on the perspective of Cultural-Historical Theory (VYGOTSKY), Activity Theory (LEONTIEV) and Teaching-Orienting Activities (MOURA). In order to obtain the data, the planning moments were recorded in audio. In the school context, the actions were filmed and photographed and a field diary was used. Each undergraduation student reported and reflected about the daily action in the classroom and in the research some field diaries were used. The data analysis was based on episodes (MOURA, 2004) that are understood as fragments that explain the empirical data of the research that will turn into scientific data, from the researcher's perspective. For this analysis, we set three axes: The child and his/her main activity; Educational planning in Early Childhood Education; Experiences in the school context. As results, the undergraduation students understood the importance of intentionally planning from the child's main activity. They also understood that the game has its seriousness in developing children's conscience in each action performed, broadening the idea of him/herself to the idea of a subject who has a social role in human relations. At the same time, they learned based on their frustration as well as realized that are not all school contexts that ponder this activity based on children's need.